Identifikasi Sebaran Endapan Nikel Laterit Berdasarkan Data Pengeboran PT. Timah Investasi Mineral Kecamatan Kabaena Barat Kabupaten Bombana Provinsi Sulawesi Tenggara - Anwar, Adrian (Program Studi Teknik Pertambangan, Fakultas Teknik, Universitas Sulawesi Tenggara, 2024)
Drilling is one of the exploration activities carried out with the aim of obtaining samples of excavated materials. In addition, drilling also aims to determine the geological structure, rock samples and groundwater levels. This research was conducted at PT Timah investasui mieneral, which is one of the mineral mining companies located in kabaena barat sub-district, bombana district, southeast Sulawesi province. The purpose of this study is to determine the direction of distribution and volume of nickel laterite deposits obtained from drilling data. In addition, the purpose of this study is to get an overview of the direction of distribution of nickel laterite deposits in 3D and the volume of nickel ore in the study area. The data obtained from drilling include collar data, assay data, survey data and lithology data. The results of the research conducted show the direction of distribution of nickel laterite deposits that have high levels spreading towards the west and south. The volume of nickel laterite deposits in the study area is 376,920 m³. The direction of distribution and volume of lateritic nickel deposits in the study area were obtained from the results of processing based on the surpac application.